Skew Injective Modules Relative to Torsion Theories - Hamid, Mohanad Farhan; Abbas, Mehdi Sadik (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The purpose of this paper is to extend results about skew injective modules to a torsion theoretic setting. Given a hereditary torsion theory t a module M is called t-skew injective if all endomorphisms of t -dense submodules of M can be extended to endomorphismsof M. A characterization of t skew injectivity using split short exact sequences is given.